BRAIN DISORDERS ASSOCIATED WITH DEMENTIA - Anton Coenen (MANASA, 2016)
This paper addresses the mental decline and dementia of patients suffering from brain disorders. The most common of these neurological illnesses is Alzheimer’s disease, characterized by a progressive atrophy of cortical brain areas. Alzheimer’s disease accounts by far for the largest part of all dementias and is presently one of the most serious disorders, causing an immense burden on patients and society. Vascular dementia is noticed when the brain’s supply of blood is disrupted by strokes or other vessel pathologies and just as in Alzheimer’s this leads to cortical atrophy with almost identical symptoms. Since the distinction between Alzheimer’s and vascular dementia is a gradual one, mixed pathologies are rather common. Rarer causes of dementia are frontotemporal dementia, with pathologies mainly in frontal and temporal brain regions, Parkinson’s disease with atrophy in basal ganglia which leads to motor disturbances and at times to mental decline, Lewy body dementia caused by abnormal deposits in the brain resulting in considerable damages of neural cells, and Huntington’s disease, a genetic disorder with widely dispersed brain atrophy characterized by mixed Alzheimer’s and Parkinson’s symptoms. Presently, for the most part the cease of the progressive course of all these disorders is not possible. The last two disorders mentioned in this paper are normal pressure hydrocephalus, with a reduced absorption of ventricular fluid, and Korsakoff’s syndrome, caused by a deficiency of vitamin B1. In normal pressure hydrocephalus a brain shunt may reverse the pathological symptoms, while a vitamin B1 diet could improve the symptoms of Korsakoff’s syndrome. Diagnosis, symptoms and pathologies of all disorders are presented in this paper.